A cultural route proposal for historical baths on the Kırkçeşme water system - Aydin, Beste Nur I. S. K. E. N. D. E. R.; Polat, Elvan Ebru O. M. A. Y. (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
In recent years, studies on water-related values have intensified on international platforms. Istanbul is one of the world's important water cities with its historical water structures that are part of a complex system. This study focuses on the evaluation of the public baths located in the K & imath;rk & ccedil;e & scedil;me Water System largest water system in Istanbul. Aiming for the cultural, environmental, and economic continuity of water-related historical assets, an integrated preservation approach for the existing traces of the historical water system is examined focusing on public baths. An increasing number of public baths are used in their original function with their full authenticity. They are also re-used for contemporary art and cultural activities regarding to their spatial opportunities. Cultural routes provide a versatile preservation methodology, also offering innovative solutions for the integration of historic assets into contemporary life. The study contains an evaluation of several texts, charters, and recommendations clarifying the systematics of cultural routes and their criteria. Evaluating the data, regarding their historical values and also current conditions, public baths redefined as a cultural route element of water systems have the opportunity to be an effective method in the holistic preservation approach.
Keywords: Assets related to water; bath (hamam); cultural routes; historical water systems; K & imath; rk & ccedil; e & scedil; me Water System; Architecture